Antifungal Activity of Selected Medicinal Plants Against Grey Mold Disease and Extension of Strawberry Shelf Life - Rashid, Tavga Sulaiman; Aziz, Brwa Azad (Zanco Journal of Pure and Applied Sciences, 2025)
Botrytis cinerea is the causal agent of grey mold disease in many plant species and presents serious losses cost problems globally; hence, it has to be controlled. This research work was aimed at ascertaining how aqueous extracts of selected medicinal plants work against B. cinerea and extend the shelf life of strawberry fruits. For this study, the following plant materials were selected: amethyst garlic, cinnamon, cloves, sumac, ginger and pelargonium plants with the potential to inhibit the growth of the newly isolated and identified B. cinerea (accession number PQ590382) using the well diffusion method. Two concentrations were utilized: 10 and 15 mg/mL. Subsequently, Strawberry fruits were immersed in these extracts for five minutes to assess their effects on shelf life and pathogen protection. Pelargonium and amethyst garlic manifested huge antifungal effects against the growth of B. cinerea. The plant extracts have considerably extended the shelf life of fungal-inhibited strawberries, reduced their spoilage, and maintained quality compared to controls. In another application, 15 mg/mL concentration of effective extracts was sprayed on seedlings of strawberry plants to determine their effect on the incidence and severity of the disease and biocontrol efficacy. Amethyst garlic and pelargonium exhibited a considerable reduction in grey mold incidence and disease severity. The biocontrol efficacy increased to about 85% when both plants were combined. These results indicate that the extracts of medicinal plants could act as natural and efficient substitutes of synthetic fungicides for grey mold management and the extension of strawberry postharvest life.